Direct ink writing of forsterite porous structure - Tan, Wei Shin (2024)
Additive manufacturing (AM), which also known as 3D printing. Its popularity has soared due to its design flexibility, rapid prototyping, and reduced material waste. For example, biomedical engineering in recent years is aiming to achieve bone regeneration by 3D printing due to its ability to control precisely the porous structure for bioceramic. Magnesium-based bioceramics, such as forsterite emerged as a new class of promising biodegradable materials, due to its good degradation and biocompatibility. Nowadays, 3D printing material with forsterite primarily uses water-based solvents. Beside water-based, organic solvents provide some additional advantages such as better mechanical properties. Therefore, the main objective of this project is to obtain the optimum formulation of forsterite with organic solvents. Additionally, the rheology and physical properties are also studied. The study began with synthesis of forsterite powder. Then, different formulations from 35 vol% to 45 vol% of forsterite loading, 300 g/L to 400 g/L of binder concentration, 15 vol% of plasticiser and 10 vol% of dispersants are tested. The combination of 43 vol% and 40 vol% with binder concentration of 400 g/L showed the best result in printability test. 43 vol% forsterite loading ink shows greater storage modulus and loss modulusthan 40 vol%, which had 28.05 Pa of yield shear stress and 4183.60 Pa of flow shear stress. Sintered part of 43 vol% also have better performance than 40 vol% in terms of physical properties such as dimension shrinkage at 18.83 %, weight reduce at 17.04 % and density at 2.70 g/cm3. 43 vol% ink also has greater hardness than 40 vol% ink. In conclusion, the optimum formulation of forsterite DIW ink is 43 vol% forsterite loading, 400 g/L binder concentration, 32 vol% binder solution, 15 vol% plasticiser and 10 vol% dispersant. Thus, this study provides reference for the future study of forsterite organogel ink.